REPLACEMNET OF GOVERNORS PLEASURE OF THE PRESIDENT A CONSITUTIONAL CAMOUFLAGE (International Journal of Food and Nutritional Sciences, 2019)
The constitutional intricacies surrounding the replacement of Governors at the pleasure of thePresident, examining the potential camouflage embedded within this constitutional provision.In many democratic nations, the appointment and removal of Governors are governed byconstitutional frameworks designed to ensure stability, autonomy, and the separation ofpowers between executive and legislative branches. However, the provision allowing thePresident to replace Governors at their pleasure raises concerns about the potential abuse ofpower and erosion of democratic principles.